Corporate Work Satisfaction: An Empirical Investigation on the Employees of Mobile Phone Companies in Bangladesh - Ashraf, Mohamad A.; Joarder, Mohd. H. R. (UI Scholars Hub, 2010)
Determining optimal employee work satisfaction is a key to the success of any business that relies on a variety of organizational and psycho-economic factors. This study was conducted to identify those key factors, which are responsible to influence on the overall work satisfaction in the fast-gowing mobile phones companies in Bangladesh. The phone companies, which are included here in the study, are Grameen Phone (GP), Bangla Link, and Aktel. The factors included in the investigation as independent variables are Compensation Package, Supervision, Career Growth, Training and Development, Working Atmosphere, Company Loyalty, and Performance Appraisal. The result indicates that training and performance appraisal, work atmosphere, compensation package, supervision, and company loyalty are the key factors that impact on work satisfaction of the employee of these companies. The study also finds that the employees of these three companies possessed above of the moderate level and positive attitude towards work satisfaction, which could be nudged up to excellent status of the satisfaction of the employess if the management takes those identified factors with a little more rigorous weight into their considerations and modify their employee retention policy further accordingly.